Diethyl phosphite-mediated switchable synthesis of bis(imidazoheterocycles) derived disulfanes and sulfanes using imidazoheterocycles and octasulfur - Reddy, Raju Jannapu; Shankar, Angothu; Kumar, Jangam Jagadesh; Sharadha, Nunavath; Krishna, Gamidi Rama (New Journal of Chemistry, 2022)
A practical and highly efficient oxidative dual C-H sulfenylation of imidazoheterocycles using odorless, inexpensive elemental sulfur in DMSO to synthesize sulfur-bridged imidazoheterocycles under metal-free conditions is reported. The amount of diethyl phosphite and sulfur powder most attractively permits a tunable synthesis of bis(imidazoheterocycle)disulfanes and bis(imidazoheterocycle)sulfanes in good to high yields. A comprehensive substrate scope with a broad range of functional group tolerance was realized, and the efficacy of the process was proved at gram-scale reactions. Next, the bis(imidazopyridine)disulfanes were smoothly reacted with various indoles under similar conditions to form the corresponding imidazo[1,2-a]pyridine-indole-derived thioethers in high yields. A plausible mechanism has been proposed based on the control experiments.

Design and synthesis of novel quinazolinyl-bisspirooxindoles as potent anti-tubercular agents: an ultrasound-promoted methodology - Allaka, Bhargava Sai; Basavoju, Srinivas; Rekha, Estharla Madhu; Sriram, Dharmarajan; Krishna, Gamidi Rama (Molecular Diversity, 2023)
The essential need for the potent anti-tubercular (anti-TB) agents with high selectivity and safety profile prompted us to synthesize a new series of quinazolinyl-bisspirooxindoles. The title compounds were synthesized by one-pot multicomponent [3 +2] cycloaddition reaction under ultrasonication. Further, in vitro anti-TB activity was evaluated against Mycobacterium tuberculosis H37Rv. Among the screened compounds, two compounds (4q and 4x) showed potent activity with MIC value 1.56 mu g/mL and four compounds exhibited significant activity (MIC =3.125 mu g/mL), and also cytotoxicity studies against RAW 264.7 cell lines reveal that most active compounds were less toxic to humans. In addition, in order to demonstrate the inhibitory properties, molecular docking studies were carried out and the results showed that the target compounds have good binding energy and better binding affinity within the active pocket, thus these compounds may consider to be as potent inhibitors toward selective targets.
Keywords: anti-tubercular activity; bisspirooxindoles; Cytotoxicity screening; Molecular docking studies; ultrasonication

Divergent access to polycyclic spiro- and fused-N,O-ketals through Bi(OTf)3-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines and alkynols - Nakate, Ashwini K.; Kataria, Priyanka; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Chemical Communications, 2024)
Bismuth(iii) triflate-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines (derived from saccharin) and alkynyl alcohols (4-pentyn-1-ols and 5-hexyn-1-ols) has been reported. This cascade annulation provides a diverse array of polycyclic spiro-and-fused N,O-ketals with excellent substrate scope, good isolated yields, and diastereoselectivities under mild reaction conditions.

Depolymerization of waste polycarbonates to value-added products - Padhi, Ganeshdev; Pansare, Vaibhav Ramachandra; Bajpai, Priyam; Krishna, Gamidi Rama; Vanka, Kumar; Barsu, Nagaraju (ChemSusChem, 2025)
Additive free aminolysis method developed for the depolymerization/upcycling of polycarbonates. We report here chemical recycling of polycarbonate under ambient conditions to get its monomer bisphenol A, monoaminocarbamate and biscarbamates in 1 : 2 : 1 ratio respectively. By employing the secondary amine as the aminating reagent, facilitates the depolymerization to work under additive/catalyst free conditions. The developed method deals with depolymerization of waste polycarbonates and works even with late-stage amine derivatives such as amoxapine and desloratadine which are drugs molecules known to treat neurotic disorders and allergies respectively. The reaction can be scaled up and works with similar efficacy which depicts the efficiency of the depolymerization of wasteend-of-life polycarbonate plastic waste. The biscarbamate and bisphenol-A was further subjected for the post functionalization to obtain amides and phenol in good yields. Developed additive/catalyst free aminolysis of waste polycarbonates to carbamates and monomer BPA at ambient conditions. Variety of secondary amines were screened including the late stage amine derivatives like amoxapine and desloratadine which delivered the expected products successfully. Later the developed methodology was even applied for the different end-of-life polycarbonates with the secondary amine and achieved the depolymerization without any obstacle. Further carried out the scale up reaction and derivatization of carbamates and BPA to amide and phenol synthesis. image
Keywords: Aminolysis; carbamates; depolymerization; End-of-life; Polycarbonate